2023
DOI: 10.1039/d2cs00217e
|View full text |Cite
|
Sign up to set email alerts
|

Rationalization of passivation strategies toward high-performance perovskite solar cells

Abstract: This review systematically outlines chemical, physical, energetic and field-effect passivation for perovskite solar cells with their corresponding advanced characterization techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
113
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(113 citation statements)
references
References 198 publications
0
113
0
Order By: Relevance
“…[ 47 ] At present, the reported methods mainly focus on the elimination of FA + defects on the surface of perovskite film or in perovskite bulk, while elimination and passivation of FA + defects at perovskite buried interface is also crucial to the quality of perovskite film, efficiency and stability of the PSCs. [ 48 ] It is regrettable that there are few reports on the improvement of device performance by suppressing the FA + defects and/or nonradiative recombination centers at perovskite buried interface.…”
Section: Introductionmentioning
confidence: 99%
“…[ 47 ] At present, the reported methods mainly focus on the elimination of FA + defects on the surface of perovskite film or in perovskite bulk, while elimination and passivation of FA + defects at perovskite buried interface is also crucial to the quality of perovskite film, efficiency and stability of the PSCs. [ 48 ] It is regrettable that there are few reports on the improvement of device performance by suppressing the FA + defects and/or nonradiative recombination centers at perovskite buried interface.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the TRPL spectra shown in Figure f showed that the PL lifetime (τ) of the HA 2 PbI 2 Br 2 /FACs film was much longer (781.88 ns) than that of the HAFAPbI 3 Br/FACs film (436.16 ns), as summarized in Table S2. The enhancement in fluorescence intensity and the prolongation of the carrier lifetime are an indication of defect passivation enabled by HA 2 PbI 2 Br 2 since trap states have been reduced, and non-radiative recombination has been greatly inhibited at both top and buried interfaces. , To assess the thermal stability of the thin films, the HAFAPbI 3 Br/FACs and HA 2 PbI 2 Br 2 /FACs films were placed on a 100 °C hot plate in a nitrogen glovebox. The HAFAPbI 3 Br/FACs thin film decomposed significantly with noticeable characteristic peaks of PbI 2 appearing, and HAFAPbI 3 Br disappeared (Figure S22a), indicating the metastability of the low-dimensional perovskite HAFAPbI 3 Br.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Therefore, stabilizing exposed surface sites where these defects are more likely to form and suppressing the movement of the ions in the perovskite should be able to reduce the formation of deep level traps. Coordinating or adsorbed molecules, such as Lewis acids/bases, could help in this aspect, as they likely create some covalent bond and/or electrostatic interactions with these defects . In particular, zwitterions would be particularly worthy of further study for defect passivation, as their combination of positive and negative functional groups may enable simultaneous passivation of defects with either charge.…”
Section: Challenges and Solutions For Tin-containing Perovskite Solar...mentioning
confidence: 99%